Achillea aleppica and Achillea arabica (Asteraceae) Phytochemical FT-IR Analysis - Basel Saleh (Journal of Stress Physiology & Biochemistry, 2024)
Achillea genus is a flowering, aromatic and perennial herbs, and widespread all over the world. Plants phytochemical analysis has a capital role in pharmaceutical and medicine preliminary studies. Two medicinal Achillea species of A. aleppica DC and A. arabica Kotschy grown wild in the Middle-Southern regions of Syria were investigated for their phytochemical analysis using fourier-transform infrared (FT-IR) spectroscopy. FT-IR spectra highlighted 11 and 12 functional groups characteristics for A. aleppica and A. arabica species, respectively; of which 9 were common between the two studied species [Aromatics (1), Ethers (3), Carboxylic acids (2), Olefinic (alkene) (1), Alkanes (1) and Aliphatic primary amine (1) groups]. These constituents have been previously investigated for different biological activities. The current study could consider as the first report regarding FT-IR Achillea analysis.